Presenting Multiple Drug Alerts in an Ambulatory Electronic Prescribing System - Xie, M.; Weinger, M.B.; Gregg, W.M.; Johnson, K.B. (Applied Clinical Informatics, 2014)
Objective: This study explores alternative approaches to the display of drug alerts, and examines whether and how human-factors based interface design can be used to improve the prescriber’s perception about drug alert presentation, signal detection from noisy alert data, and their comprehension of clinical decision support during electronic prescribing.Methods: We reviewed issues with presenting multiple drug alerts in electronic prescribing systems. User-centered design, consisting of iterative usability and prototype testing was applied. After an iterative design phase, we proposed several novel drug alert presentation interfaces; expert evaluation and formal usability testing were applied to access physician prescribers’ perceptions of the tools. We mapped drug alert attributes to different interface constructs. We examined four different interfaces for presenting multiple drug alerts.Results: A TreeDashboard View was better perceived than a text-based ScrollText View with respect to the ability to detect critical information, the ability to accomplish tasks, and the perceptional efficacy of finding information.Conclusion: A robust model for studying multiple drug-alert presentations was developed. Several drug alert presentation interfaces were proposed. The TreeDashboard View was better perceived than the text-based ScrollText View in delivering multiple drug alerts during a simulation of electronic prescribing.Citation: Xie M, Weinger MB, Gregg WM, Johnson KB. Presenting multiple drug alerts in an ambulatory electronic prescribing system: A usability study of novel prototypes. Appl Clin Inf 2014; 5: 334–348 http://dx.doi.org/10.4338/ACI-2013-10-RA-0092
Keywords: Electronic prescribing; clinical decision support; drug alert; adverse drug event; user interface